Efektivitas Google Sites dalam Mendukung Pembelajaran Eksponen dan Logaritma Berbasis Student-Centered Learning - Yandara Gapila Patihah; Surya Amami Pramuditya (Journal of Education and Teaching Learning, 2026)
This study aims to develop and examine the effectiveness of Google Sites–based instructional media for exponent and logarithm topics in supporting student-centered learning (SCL). The research employed a Research and Development (R&D) approach using the ADDIE model. The research subjects included experts (7 teachers) for the validity test and users (2 teachers and 80 senior high school students) for the practicality test. Data were collected through Likert-scale questionnaires and open-ended feedback, then analyzed using descriptive quantitative and qualitative methods. The expert validation results indicate that the media is highly feasible, categorized as Very Good (score: 3.90), particularly in technical aspects and instructional feasibility. User feedback confirms that the media is Good (score: 3.48), with technical elements identified as its primary strength. Qualitative findings reveal areas for further development, including improvements in contextual aesthetics, the addition of search and dark mode features, and enrichment of content through teacher-produced instructional videos. The study concludes that the developed Google Sites media is effective as a supporting tool for SCL, as it promotes learner autonomy through strong technical accessibility and adequate pedagogical design. The implication is that teachers can adopt this media to expand the variety of independent learning activities, provided that future development enhances interactivity and content personalization.